2011
DOI: 10.1007/s00464-011-1820-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of band erosion: feasibility and safety of endoscopic band removal

Abstract: Despite a few complications, endoscopic removal seems to be the procedure of choice for the treatment of band erosion. It allows quick resumption of oral feeding and rapid discharge of patients and appears to be safer and more effective than laparoscopic removal. Conversion to surgery is unlikely but possible. Therefore, the authors always recommend that the procedure be performed in the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 19 publications
(21 reference statements)
2
17
0
1
Order By: Relevance
“…In our patient, we did not repair the stomach after band removal in the reported case, and gastric fistula did not occur. Our opinion is supported by Mozzi et al, 14 who suggested that gastric leak should be anticipated after surgical anterior gastrostomy and not after band removal. Band migration was reported in many previous studies.…”
Section: Discussionsupporting
confidence: 74%
“…In our patient, we did not repair the stomach after band removal in the reported case, and gastric fistula did not occur. Our opinion is supported by Mozzi et al, 14 who suggested that gastric leak should be anticipated after surgical anterior gastrostomy and not after band removal. Band migration was reported in many previous studies.…”
Section: Discussionsupporting
confidence: 74%
“…The gold standard investigative modality is endoscopy [5]. CT is another option, although such tool is more useful in detection of associated complications such as extend, site and type of perforation and/or contaminations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors believe, such procedure is safe and feasible in circumstances when standard laparoscopic retrieval is not possible. Placement of a new gastric band is usually delayed for a period of 3 months in such cases [3, 5]. In the reported case, patient made an uneventful recovery and was discharged 3 days following the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Intragastric erosion may be partial or complete. Its causes include small gastric wall injuries incurred during band placement, overdistention of the band with resultant gastric wall ischemia, band site infection, and inflammatory reaction (35)(36)(37). Adhesions from widespread dissection during band placement and the use of nonsteroidal anti-inflammatory drugs also may contribute to erosion (35)(36)(37).…”
Section: Intragastric Erosionmentioning
confidence: 97%